Experimental study on heat and mass transfer characteristics between a novel ionic liquid and air under low-humidity conditions. (1st December 2022) - Cao, Bowen; Yin, Yonggao; Zhang, Fan; Tong, Shoubao; Che, Chunwen; Chen, Wanhe; Ji, Qiang; Xu, Guoying; Li, Xiao
Highlights: The dehumidification and regeneration performance of an adiabatic falling-film device working with a novel ionic liquid is experimentally studied. A specialty of this report is the operation under rather low air temperature as well as low absolute humidity. The heat and mass transfer characteristics between the novel IL and moist air is investigated and compared with LiBr-H2 O. Correlations for predicting the coupled heat and mass transfer coefficient of the novel IL in dehumidification and regeneration process are developed. Graphical abstract: Image, graphical abstract Abstract: Functional ionic liquids (ILs) are a promising alternative to traditional liquid desiccants. This work is mainly concerned with an experimental investigation on the dehumidification and regeneration performance of an adiabatic falling-film device working with a novel ionic liquid (IL). A specialty of this report is the operation under rather low air temperature as well as low absolute humidity. The effect of air and solution volume flow on the coupled heat and mass transfer coefficient was evaluated based on the state parameters of air and solution by means of the NTU - Lef model. Additionally, aqueous lithium bromide solution (LiBr-H2 O) was used for comparison. The results indicated that both IL and LiBr-H2 O can dehumidify moist air to nearly 2.2 g/kgda, and the regeneration rate of IL is significantly larger than that of LiBr-H2 O. The heat and mass transfer coefficient of IL in dehumidification process is less than that of LiBr-H2 O, while the regeneration process is the opposite. It is found that the low wettability of IL on the surface of falling-film plate limits its excellent dehumidification potential, whereas its high mass transfer coefficient in the regeneration process makes up for the disadvantage of poor regeneration potential. Besides, a new correlation for the coupled heat and mass transfer coefficient of IL is proposed. From the perspective of operation optimization, increasing the wettability of IL on falling-film plate will significantly improve the dehumidification rate, and the optimal flow range of IL needs to be considered in the regeneration process. This study establishes a basis for the optimization of heat and mass transfer process between ILs and moist air, and provides guidance for the application of liquid desiccant dehumidification under low-humidity conditions.